RESERPINE CONTENT OF RAUWOLFIA SERPENTINA IN RESPONSE TO GEOGRAPHICAL VARIATION - HAREESH KUMAR V; NIRMALA; SHASHIDHARA S; RAJENDRA C E (International Journal of Pharma and Bio Sciences, 2010)
Important requirement in the evaluation of herbal drug include the estimation of active constituent. Different factors like climate, altitude, rainfall and other conditions responsible for growth of plants may affect the content of active constituents. Collection of drug from different geographical sources can give useful conditions required for the production of maximum amount of secondary cell constituents. Rauwolfia Samples were collected from four different parts of southern India. HPLC chromatogram was developed for standard reserpine. Different samples were extracted using methanol and extracts were subjected to HPLC analysis to find out the content of Reserpine for preliminary information about the conditions that may influence on production of active constituents. Significant variation in the content of reserpine has been recorded.